Hook modification to reduce rockfish and Pacific spiny dogfish bycatch in the U.S. West Coast Pacific halibut longline fishery - Dylan S. Heppell; Mark J. M. Lomeli; W. Waldo Wakefield; Bent Herrmann; Claude L. Dykstra; Ian J. Stewart (Reviews in Fish Biology and Fisheries, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

P29-02 Comparative assessment of 24 poorly soluble, low toxicity dusts after short-term exposure - A. Herrmann; L. Puente; M. Dammann; L. Ma-Hock; H. Stratmann (Toxicology Letters, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Can pots be an alternative fishing gear to gillnets? A Mediterranean case study - M. Virgili; A. Petetta; B. Herrmann; K. Cerbule; S. Guicciardi; G. La Manna; L. Malvarosa; D. Li Veli; G. Barone; A. Lucchetti (Reviews in Fish Biology and Fisheries, 2024)
Small-scale coastal fisheries in the Mediterranean often employ gillnets, a widely used gear worldwide. The disadvantages of gillnets in this fishery include high bycatch levels of unwanted species and consequent discards. Moreover, spatial conflict with other gears and dolphin depredation often results in considerable economic loss. Alternative fishing methods are being tested. This study investigated whether, in small-scale fisheries in the Adriatic Sea, pots can ensure sustainable harvest of mantis shrimp ( Squilla mantis ), a major target demersal species in terms of landings, and possibly replace traditional gillnets. We adopted a multidisciplinary approach to investigate the catch efficiency, biological impact, and socio-economic effects of the two fishing methods. We found different species compositions in gillnet and pot catches. Gillnets yielded a greater number of discarded species of no commercial value, whereas pots caught a greater amount of mantis shrimp. Finally, a profit analysis indicated that pot fishery has the potential to increase profits for the commercial fishing industry. This study suggests that pots provide a more sustainable fishing method, both in terms of revenue and environmental impact.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Do ticks exhibit repeatable individual behaviors? - Hugh Lefcort; Matthew L. Hovancsek; Lindsey A. Bell; Erin K. Ellinwood; Elizabeth M. Freisinger; Katelin G. Herrmann; Jalisa R. Lau (Experimental and Applied Acarology, 2023)

Simulation of steam/air leakage through small-scale cracked concrete specimen - L. Bahr; J. Sievers; M. Zemann; N. Herrmann (European Journal of Environmental and Civil Engineering, 2022)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Connectivity increases trophic subsidies in fragmented landscapes - Christine L. Hawn; John D. Herrmann; Sean R. Griffin; Nick M. Haddad (Ecology Letters, 2018)
Landscape corridors mitigate the negative effects of habitat fragmentation by increasing dispersal. Corridors also increase biodiversity in connected habitat fragments, suggestive of metacommunity dynamics. What is unknown in this case is the mechanisms through which metacommunity dynamics act. Working in a large‐scale fragmentation experiment, we tested the effect of corridors on the movement of prey species and subsequent effects on predator nutrition (which we call trophic subsidies). We enriched plants of central patches with 15 N, then measured δ 15 N in green lynx spiders, the most abundant insect predator, in patches that were either connected to or isolated from the enriched patch. We found that corridors increased prey movement, as they increased spider δ 15 N by 40% in connected patches. Corridors also improved spider body condition, increasing nitrogen relative to carbon. We suggest a novel mechanism, trophic subsidies, through which corridors may increase the stability or size of populations in connected landscapes.

Measurements of PM10 ions and trace gases with the online system MARGA at the research station Melpitz in Germany – A five-year study - B. Stieger; G. Spindler; B. Fahlbusch; K. Müller; A. Grüner; L. Poulain; L. Thöni; E. Seitler; M. Wallasch; H. Herrmann (Journal of Atmospheric Chemistry, 2018)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prevention of unpredictable chronic stress-related phenomena in zebrafish exposed to bromazepam, fluoxetine and nortriptyline - Matheus Marcon; Ana P. Herrmann; Ricieri Mocelin; Cassiano L. Rambo; Gessi Koakoski; Murilo S. Abreu; Greicy M. M. Conterato; Luiza W. Kist; Maurício R. Bogo; Leila Zanatta; Leonardo J. G. Barcellos; Angelo L. Piato (Psychopharmacology, 2016)

Connectivity from a different perspective: comparing seed dispersal kernels in connected vs. unfragmented landscapes - John D. Herrmann; Tomás A. Carlo; Lars A. Brudvig; Ellen I. Damschen; Nick M. Haddad; Douglas J. Levey; John L. Orrock; Joshua J. Tewksbury (Ecology, 2016)
Habitat fragmentation can create significant impediments to dispersal. A technique to increase dispersal between otherwise isolated fragments is the use of corridors. Although previous studies have compared dispersal between connected fragments to dispersal between unconnected fragments, it remains unknown how dispersal between fragments connected by a corridor compares to dispersal in unfragmented landscapes. To assess the extent to which corridors can restore dispersal in fragmented landscapes to levels observed in unfragmented landscapes, we employed a stable‐isotope marking technique to track seeds within four unfragmented landscapes and eight experimental landscapes with fragments connected by corridors. We studied two wind‐ and two bird‐dispersed plant species, because previous community‐based research showed that dispersal mode explains how connectivity effects vary among species. We constructed dispersal kernels for these species in unfragmented landscapes and connected fragments by marking seeds in the center of each landscape with 15 N and then recovering marked seeds in seed traps at distances up to 200 m. For the two wind‐dispersed plants, seed dispersal kernels were similar in unfragmented landscapes and connected fragments. In contrast, dispersal kernels of bird‐dispersed seeds were both affected by fragmentation and differed in the direction of the impact: Morella cerifera experienced more and Rhus copallina experienced less long‐distance dispersal in unfragmented than in connected landscapes. These results show that corridors can facilitate dispersal probabilities comparable to those observed in unfragmented landscapes. Although dispersal mode may provide useful broad predictions, we acknowledge that similar species may respond uniquely due to factors such as seasonality and disperser behavior. Our results further indicate that prior work has likely underestimated dispersal distances of wind‐dispersed plants and that factors altering long‐distance dispersal may have a greater impact on the spread of species than previously thought.

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes - H. Hupfer; M. Swiatek; S. Hornung; R. G. Herrmann; R. M. Maier; W.-L. Chiu; B. Sears (Molecular Genetics and Genomics, 2008)

Lychee tree parameters for water balance modeling - K. Spohrer; C. Jantschke; L. Herrmann; M. Engelhardt; S. Pinmanee; K. Stahr (Plant and Soil, 2006)

Frequency of Norovirus in stool samples from patients with gastrointestinal symptoms in Switzerland - R. Fretz; L. Herrmann; A. Christen; P. Svoboda; O. Dubuis; E. H. Viollier; M. Tanner; A. Baumgartner (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Genetic distinction of wildcat ( Felis silvestris ) populations in Europe, and hybridization with domestic cats in Hungary - M. Pierpaoli; Z. S. Birò; M. Herrmann; K. Hupe; M. Fernandes; B. Ragni; L. Szemethy; E. Randi (Molecular Ecology, 2003)
The genetic integrity and evolutionary persistence of declining wildcat populations are threatened by crossbreeding with widespread free‐living domestic cats. Here we use allelic variation at 12 microsatellite loci to describe genetic variation in 336 cats sampled from nine European countries. Cats were identified as European wildcats ( Felis silvestris silvestris ), Sardinian wildcats ( F. s. libyca ) and domestic cats ( F. s. catus ), according to phenotypic traits, geographical locations and independently of any genetic information. Genetic variability was significantly partitioned among taxonomic groups ( F ST = 0.11; R ST = 0.41; P F ST = 0.07; R ST = 0.06; P

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)